Developing speaking skills module for engineering students - Noor Raha, Mohd Radzuan; Fatimah, Ali; Hafizoah, Kassim; Haslinda, Hashim; Najah, Osman; Ramle, Abid (Common Ground Publishing Pty Ltd, 2008)
To increase the employability of engineering graduates, communication skills are crucial. In a dialogue between the industries and Malaysian public universities in 2002, it was highlighted that most local graduates lack communication skills (Tengku Mahaleel, 2002). Thus, to meet and exceed the expectation of all stakeholders, universities need to review the language and communication courses and teaching approaches. Splitt (1993) states that, “the challenge is to provide better ways for faculty to work with students, and to help them enhance their people-related skills. We need people who can work with other people, who can communicate, be inventive, creative, and have ideas and the courage to see them through”. Thus, taking into consideration these challenges, this research aims to develop an effective module of speaking skills for Universiti Malaysia Pahang’s (UMP) engineering students. The objectives of the research are (1) to develop students’ oral competency through various speaking activities based on workplace case scenarios and (2) to enhance students’ level of confidence as they engage in different types of communicative events. A total of 28 and 16 engineering students were engaged as subjects in the study for experimental and control group respectively. The experimental group was given treatment using the speaking skills module developed. To assess the effectiveness of the module, pre test and post test were conducted to both groups using Malaysian University English Testing (MUET) system. Personal Report of Communication Apprehension (PRCA-24) form was also administered to both groups during the pre and post tests to measure their level of communication apprehension. For the experimental group, the results show there was a considerable improvement in their oral competency as well as a significant reduction of communication apprehension level after the treatment.